Analysis of Islamic Faculty of Economics and Business Student Intensity in Using Online Transportation Services - Qirsy Halimatus Sa’diyah; Ridwan Akbar Ramadhan; Abdillah Dimas Pratama; Henny Saraswati; Wahyu Hidayat; Budi Sudrajat; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2022)
The purpose of this research is to explain the costs associated with online transportation, especially for students of the SMH Banten State Islamic University who live around Palima and its surroundings, and to show that online transportation is a viable alternative for these students. This study used a quantitative method using observation data collection methods, interviews, and document studies. Students of the Faculty of Economics and Islamic Business at SMH Banten State Islamic University use online transportation facilities near Palima and its surroundings and are used by FEBI students.